The Cultural Heritage of Kenya's Swahili Muslims: the Contributions and Breaks in Islamic History - Hidayatullah, Muhammad Yunus; Basyir, Abd A'la (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This article aims to explain the contributions and discontinuities of Islamic history in the cultural heritage of Kenya's Swahili ethnic Muslim traditions. Therefore, in this article the author formulates two problems: 1) what is the journey of Islam in Kenya 2) what is the role and contribution of Islam to Kenyan Swahili civilisation. The research method used in this paper is a historical research method that includes heuristic, verification, interpretation and historiography stages. The focus of this article is to describe the beginning of the journey of Islam to dominance in Kenya, which was then replaced by Christian dominance. And to uncover traces of the cultural heritage of Kenya's Swahili Muslims. The results of this research show that there was a break in Islamic history when Kenya entered the colonial era. This had an impact on the spread of Islam and the cultural traditions of the Swahili ethnic Muslim culture of Kenya. Islam has also played an important role and contribution, this is especially true of the Swahili ethnic culture on the coast of Kenya. It can therefore be concluded that it is very important for the Swahili ethnic group living on the coast to continue to maintain and preserve Islamic culture as their identity, which has existed for several centuries.